PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS V MELALUI MODEL PBL DENGAN BERBANTUAN MEDIA AJAR “MIMBAR” - Rona Fristi Febbilla; Uswatun Ni’mah, Diana Ermawati (ADISAM PUBLISHER, 2025)
This research aims to improve critical thinking skills in mathematics subjects for fifth grade students at SDN Ngemplak Kidul 03 through the PBL model using the help of the pulpit teaching media. The method in this research is Classroom Action Research which was conducted in March-June 2024 at SDN Ngemplak Kidul 03. The subjects in this research were class V students at SDN Ngemplak Kidul 03, totaling 13 students. The object of this research is students' critical thinking abilities using the Problem Based Learning method assisted by pulpit teaching media. The data collection techniques used in this research are observation, interviews, tests and documentation. Based on the results assisted by pulpit media can improve students' critical thinking skills in class V of SDN Ngemplak Kidul 03.of the student learning test percentage in cycle I was 79.23% and in cycle II it increased to 88.84% in the good category. Thus, it can be concluded that the use of the PBL model